Local Tax Benefits at a Distance Japan's Hometown Tax Donation Payment - Hoda, Takaaki; Dasher, Richard B. (Kobe University Social Science Research Series,, 2021)
This book discusses the concepts, types, models, and patterns of Japan's Hometown Tax Donation Payment system, to provide a clear picture of this newly developed unique and innovative fund-raising tool used by municipalities. It also sheds light on the influences that reciprocal gifts provided by each municipality to donors have on local economies by reviewing empirical works and surveys targeting local business owners and local financial institutions. A distinguishing feature of the book is that it introduces a new social finance mechanism that is unique to the Japanese market and could provide policy implications for small and medium-sized enterprises (SMEs) as well as regional development. Furthermore, the book explores the efficacy of the demand-pull approach to support-strengthening SMEs, especially in rural areas. Finally, the book identifies some lessons learned from the system with a view toward advancing research on this phenomenon and making the system efficient and sustainable. As a whole, the book can provide ample benefits to novices, academics, researchers, and policymakers interested in Hometown Tax Donation Payment, an innovative social finance tool. This is an open access book.